2005
DOI: 10.1086/502526
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal ofStaphylococcus aureusInto the Air Associated With a Rhinovirus Infection

Abstract: Virus-induced dispersal of S. aureus into the air may have an important role in the transmission of S. aureus and other bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 46 publications
1
47
1
Order By: Relevance
“…2) During a pandemic, in communities not yet affected, universally vaccinate with a safe and effective strain-specifi c infl uenza vaccine, if available. 3) During local epidemics, treat all serious clinical cases with an antibacterial agent that is effective against S. pneumoniae, S. pyogenes, H. infl uenzae, and S. aureus (including methicillin-resistant S. aureus); isolate patients with clinical cases from other patients and as many others as possible (35,(37)(38)(39). 4) Conduct pandemic-related surveillance that tracks the incidence, nature (e.g., species, affected sites, antimicrobial drug sensitivities), and outcomes of bacterial infections that complicate infl uenza cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) During a pandemic, in communities not yet affected, universally vaccinate with a safe and effective strain-specifi c infl uenza vaccine, if available. 3) During local epidemics, treat all serious clinical cases with an antibacterial agent that is effective against S. pneumoniae, S. pyogenes, H. infl uenzae, and S. aureus (including methicillin-resistant S. aureus); isolate patients with clinical cases from other patients and as many others as possible (35,(37)(38)(39). 4) Conduct pandemic-related surveillance that tracks the incidence, nature (e.g., species, affected sites, antimicrobial drug sensitivities), and outcomes of bacterial infections that complicate infl uenza cases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for brief periods and to varying degrees, affected hosts became "cloud adults" who increased the aerosolization of colonizing strains of bacteria, particularly pneumococci, hemolytic streptococci, H. infl uenzae, and S. aureus (39). For several days during local epidemicsparticularly in crowded settings such as hospital wards, military camps, troop ships, and mines-some persons were immunologically susceptible to, infected with, or recovering from infections with infl uenza virus.…”
Section: Hypothesismentioning
confidence: 99%
“…Coinfection with other respiratory pathogens can aid spread by aerosolizing pathogens that aren't ordinarily airborne [78,12,13]. Age, nutritional status, vaccination history, and other factors influence host immunocompetence, which interacts with pathogen properties to determine the intensity and duration of infection.…”
Section: Factors Causing Individual-level Variation In Infectiousnessmentioning
confidence: 99%
“…In this study, healthy adults who were experimentally infected by rhinovirus showed increase in the relative abundance of H. parainfluenzae, Neisseria subflava and S. aureus , and returned to their baseline level after the infection was cleared [34]. It has been also shown that experimental rhinovirus infection significantly increases S. aureus nasal load by 39% compared to baseline bacterial load [30]. These findings suggest that changes in the composition of respiratory microbiota following rhinovirus infection may play a role in the development of bacterial superinfection.…”
Section: Impact Of Viral Infections In the Respiratory Tract On Staphmentioning
confidence: 99%